State of fear - Crichton, Michael, 1942-2008 (London : HarperCollins, 2004)
'In Paris, a physicist dies after a visit from a beautiful stranger. In the jungles of Malaysia, a mysterious buyer purchases deadly technology. In Vancouver, a research submarine is hired for use in the waters off New Guinea. And in Tokyo, Professor John Kenner -- intelligence agent and environmental specialist -- works to uncover an unprecedented threat to the future of the entire world'--P. [4] of cover.
Includes bibliographical references.
Keywords: Ecoterrorism -- Fiction; Submarines (Ships) -- Fiction; Global warming -- Fiction; Suspense fiction, American; South Pacific Ocean -- Fiction